Seroconversion after Recombinant Hepatitis B Vaccination - Guho, Abhijit; Ahad, Md abdul; Salam, Md Abdus; Alim, Md Abdul; Haque, AKM Enamul; Islam, Quazi Tarikul (Journal of Medicine, 2010)
Background: Hepatitis B virus infection is an important public health problem with significant morbidity and mortality. Recombinant hepatitis B vaccine for the prevention of hepatitis B virus infection is in practice in different parts of the world since its availability in 1986. Government of Bangladesh has also included hepatitis B vaccine in EPI schedule since 2005. Materials and methods: This study was carried out to assess the seroconversion status among hepatitis B vaccinated individuals. A total of 190 individuals including 150 vaccinated persons and 40 non-vaccinated apparently healthy individuals were included as study population. Sources of vaccinated persons were from both EPI and non- EPI schedule of vaccination. Age and sex matched non-vaccinated individuals served as controls for the study. All individuals constituting the study population were screened for HBsAg by Immunochromatographic strip test and only HBsAg-negative persons were included for estimation of their anti-HBs titer. Results: Out of 150 vaccinated individuals, 133(88.67%) were found to have anti-HBs titer in the protective level (>10 IU/L), while 17(11.33%) individuals had anti-HBs titer below the protective level (<10 IU/L). All non-vaccinated controls had anti-HBs titers below the protective level. Regarding immune response developed among vaccinated individuals, 67.78%, 23.33% and 8.89% were good-responders, hypo-responders and non-responders respectively. Mean titer of anti-HBs was found significantly higher among recipients who received booster dose than those who received 3 doses schedule (863.39 IU/L vs. 262.40 IU/L), indicating high antibody titer develops after booster dose. Vaccinated group included 85 (56.67%) men and 65 (43.33%) women with protective level of anti-HBs titer found in 85.88% male and 92.31% female individuals. There was no significant difference of anti-HBs titer between male and female (p>0.05). Vaccinated individuals from lower socioeconomic condition have had comparatively low rate of protective antibody than people from middle and upper classes. Conclusion: Recombinant HB vaccine induces good level of protective immunity among vaccinated persons. Keywords: Hepatitis B; hepatitis B vaccine; seroconversion; Bangladesh DOI: 10.3329/jom.v11i2.5461 J MEDICINE 2010; 11 : 143-150